Ashmolean Museum. Department of Antiquities. Select Exhibition of Sir John and Lady Beazley Gifts to the Ashmolean Museum 1912-1966. Foreword by R. W. Hamilton - Anonymus, A. (1967)
Published for the Ashmolean Museum by the Oxford University Press ; espec. nos. 37-38, p. 19: Luristan bronze figures tube; 1935-43; Luristan bronze bracelet; 1966.1107.